Streamflow response to the rapid retreat of a lake‐calving glacier. Issue 20 (12th June 2016) - Moyer, Alexis N.; Moore, R. D.; Koppes, Michele N.
Abstract: There has been increasing attention over the last decade to the potential effects of glacier retreat on downstream discharge and aquatic habitat. This study focused on streamflow variability downstream of Bridge Glacier in the southern Coast Mountains of BC between 1979 and 2014, prior to and during a period in which the glacier experienced enhanced calving and rapid retreat across a lake‐filled basin. Here we combined empirical trend detection and a conceptual‐parametric hydrological model to address the following hypotheses: (1) streamflow trends in late summer and early autumn should reflect the opposing influences of climatic warming (which would tend to increase unit‐area meltwater production) and the reduction in glacier area (which would tend to reduce the total volume of meltwater generated), and (2) winter streamflow should increase because of displacement of lake water as ice flows past the grounding line and calves into the lake basin. In relation to the first hypothesis, we found no significant trends in monthly discharge during summer. However, applying regression analysis to account for air temperature and precipitation variations, weak but statistically significant negative trends were detected for August and melt season discharge. The HBV‐EC model was applied using time‐varying glacier cover, as derived from Landsat imagery. Relative to simulations based on constant glacier extent, model results indicated that glacier recession caused a decline in mean monthly streamflow of 9% in August and 11% in September. These declines in late‐summer streamflow are consistent with the results from our empirical analysis. The second hypothesis is supported by the finding of positive trends for December, January, and February discharge. Despite the modelled declines in late‐summer mean monthly streamflow, recorded discharge data exhibited neither positive nor negative trends during the melt season, suggesting that Bridge Glacier may currently be at or close to the point of peak water. Further analysis of the impact of lake‐terminating glaciers on downstream discharge is needed to refine the peak water model. Copyright © 2016 John Wiley & Sons, Ltd.